Formulasi Dan Evaluasi Sediaan Salep Luka Bakar Basis Hidrokarbon Ekstrak Etanol Daun Katang-Katang (Ipomoea Pescaprae L.) Asal Desa Seith Tahun 2023 - Nur’in Aihena; Aulia Debby Pelu; Sahril Sillehu (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Background: Ointment is a semisolid preparation used as a topical medicine, which has direct access to the skin tissues. Katang-katang is one of the medicinal plants traditionally used to treat various types of wounds. Objective: The aim of this study is to identify the secondary metabolite content of katang-katang leaves (Ipomoea pescaprae L.), create and evaluate a good and stable ointment formulation pharmaceutically, and test the irritation of the ointment for burn wounds using ethanol extract of katang-katang leaves (Ipomoea pescaprae L.). Method: The method used is experimental research, the ointment formulation is made using three formulations with different concentrations of active ingredients, with a ratio of FI 20%, FII 25%, and FIII 30%. Result: The results of the study indicate that katang-katang leaves contain flavonoids, tannins, and steroids. The study determined the formulation of a burn ointment from ethanol extract of katang-katang leaves (Ipomoea pescaprae L.). The organoleptic test results of FI, FII, and FIII showed good and stable color, odor, and shape, as well as homogeneity after one week of storage. The pH values measured were 7 for all formulations even after one week of storage. The spreading power of FI was (5.52 cm), FII was (5.88 cm), and FIII was (7.23 cm), which met the standards for good formulation. The irritation tests for all three formulas were categorized as safe. Conclusion: Based on the identification test results, the katang-katang leaves were found to contain flavonoids, tannins, and steroids. The evaluation test results for the three formulations using a hydrocarbon base showed that a good and stable burn ointment could be made from the ethanol extract of katang-katang leaves (Ipomoea pescaprae L.) without causing skin irritation.